Advances in applying Raman spectroscopy to the study of enzyme mechanisms. (16th June 2021) - Carey, Paul; Pusztai‐Carey, Marianne
Abstract: This review sets out the progress over the past 50 years, mostly in the authors' laboratory, for Raman spectroscopy in defining the precise chemical changes driving enzyme‐mediated catalysis. The spectroscopy has been enabled by advances in computer, laser and optical technologies. Derek Long's generation (including the authors of this review) has been privileged to experience many of these changes. Here, we show how Raman can define individual molecular populations at work inside bacterial cells. In addition, several satellites have spun off the main theme. These include rapid reaction applications, drug screening, and RNA‐based enzymes. These are discussed briefly, and the reader can explore the details using the references given. Abstract : *Raman difference spectrum defines chemical changes for drug inside bacteria.